Morphological characteristics of the myocardial contractile apparatus in rats under the influence of hypoxia (literature review and research perspectives) - Kobeza, P.A.; Cherkas, O.A.; Marchenko, D.G.; Khripkov, I.S. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Conducting model experiments on different age groups of laboratory rats under chronic hypoxic conditions is relevant and aids in studying structural changes in cardiac tissues from a scientific perspective. Understanding the mechanisms of heart adaptation to hypoxia. Research into cardiac adaptation to hypoxia helps uncover the mechanisms that enable the heart to function under low oxygen conditions. Studies on different age groups of rats can help determine how age affects adaptation and the ultrastructure of the heart during hypoxia. The objective of this study is to understand the impact of hypoxia on the hearts of rats at different stages of their lives, including neonates, young, and adult animals. This helps expand our knowledge of the adaptive mechanisms of the heart and may have significant implications for the normal anatomy of laboratory animals, their biological significance, and a comprehensive understanding of the ultrastructural remodeling of the components of the myocardial contractile apparatus. Methods. Systematic Literature Review, Meta-Analysis, Content Analysis, Assessment of Source Quality, Information Retrieval. Results. Chronic hypoxia affects the structure of the myocardial contractile apparatus in rats during different stages of development (from birth to 6 months) as follows: Newborn rats: Hypoxia can lead to myocardial hypertrophy and an increase in the number of capillaries to improve blood supply. 1 month after birth: Under hypoxia, there is myocardial hypertrophy, an increase in the amount of fibrous tissue, and possible vessel remodeling. 3 months after birth: Hypoxia can result in further enlargement of the myocardium, changes in structure and functional parameters, and the development of new vessels. 6 months after birth: At this stage, significant changes are possible, including hypertrophy, vessel remodeling, alterations in functional parameters, and structural peculiarities of the myocardium. Conclusion. Chronic hypoxia affects the morphology of the myocardium in rats at different stages of their development, leading to changes in size, structure, and cardiac functionality.